Quem convida é a mulher: experiências femininas e subversão nos bailes de Dança de Salão - Siqueira, Monalisa Dias de (2009)
The objective of this research is to analyze the sociability between men and women of different social and age groups in the hall-dance balls in Fortaleza. For this, the hall-dance balls had been taked of sociability spaces, beyond having been proposal an analysis of related female experiences to the aging, your body, individualization process, autonomy and affects. The hall-dance was contextualized on the city, showing the process of transition of the predominantly "familiar” balls in the social clubs, for the "new" balls, in which older women contract younger men for dancing. In this manner, was analyzed the inserion of women in the named "world of dance", as well the contractual relations between customers and dancers, and the symbolic interchange in this context.